Plant growth regulators optimization for in vitro cultivation of the orchid Guarianthe skinneri (Bateman) Dressier & W.E.Higgins Optimización de reguladores de crecimiento para el cultivo in vitro de la orquídea Guarianthe skinneri (Bateman) Dressier & W.E.Higgins - Christian Yanelly Coello (Universidad de Concepción, 2010)
An in vitro culture procedure was developed to induce shoots and roots of Guarianthe skinneri (Orchidaceae) plantlets regenerated from seed-derived protocorms on a Murashige and Skoog (MS) médium supplemented with 6-benzyladenine (BA), indole-3-acetic acid (IAA), a-naftalenacetic acid (NAA) and gibberellic acid (GA3). A máximum of 10.6 shoots was obtained with 16.1 μM NAA, 17.1 μM IAA, 6.3 x 10-9 μM GA3 and 0.0023 μM BA. A máximum of 4.0 roots on each shoot with 5.4 μM NAA, 17.1 μM IAA, 0.001 μM AG3 and 4.6 x 10-9 μM BA. Máximum shoot and root length was obtained with a minimum of GA3, but a máximum IAA. GA3, was the main factor controlling shoot and root induction and elongation. Se desarrolló un procedimiento para el cultivo in vitro para inducir brotes y raíces en las plántulas de Guarianthe skinneri (Orchidaceae) regeneradas a partir de protocormos derivados de semillas en un medio de Murashige & Skoog (MS) complementado con 6-benziladenina (BA), ácido indol-3-acético (AIA), ácido a-naftalenacético (ANA) y ácido giberélico (GA3). Se obtuvo un máximo de 10,6 brotes con 16,1 μM de ANA, 17,1 μM de AIA, 6,3 x 10-9 μM de GA3 y 0,0023 μM de BA. Un máximo de 4,0 raíces en cada brote se obtuvo con 5,4 μM de ANA, 17,1 μM de AIA, 0,001 μM de AG3 y 4,6 x 10-9 μM de BA. La longitud máxima de brotes y raíces se obtuvo con la más baia concentración de GA3, y la mayor concentración de AIA. El GA3, fue el factor principal que controló la inducción y la elongación de los brotes y raíces.